The earth's blanket : traditional teachings for sustainable living - Turner, Nancy J., 1947- (University of Washington Press, 2005)
"Turner has worked with Native peoples in the Pacific Northwest for more than thirty-five years, and generations of her indigenous teachers have given her permission to share their stories and perspectives about the natural world. Their teachings describe a rich variety of methods of harvesting, transporting, processing, storing, maintaining, and enhancing natural resources such as trees, medicinal plants, berries, root vegetables, fish, meat, and shellfish. More than just stories, these narratives underlie a belief system that informs everyday attitudes toward the earth." "The Earth's Blanket suggests how systems of traditional ecological knowledge can contribute to the modern world."--Jacket.
Keywords: Human ecology -- Philosophy.; Ethnoecology.; Philosophy of nature.; Conservation of natural resources.; Environmental protection.; Conservation of Natural Resources; Écologie humaine -- Philosophie.; Autochtones -- Écologie.; Philosophie de la nature.; Conservation des ressources naturelles.; Environnement -- Protection.; Ethnoécologie.; environmental protection.; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Sociology -- General.; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies.; Conservation of natural resources; Environmental protection; Human ecology -- Philosophy; Ethnoecology; Philosophy of nature